Urinary Protein/Creatinine Ratio in Feline Medicine: Reasons to Perform It and Its Role in Clinical Practice—A Retrospective Study - Maria Ana Fidalgo; Rodolfo Oliveira Leal; José Henrique Duarte-Correia (Animals, 2022)
This study aimed at understanding the reasons veterinarians conduct a urinary protein/creatinine ratio (UPCR) in cats, correlating it with signalment, dipstick proteinuria tests, and urine specific gravity (USG) and assessing its role in chronic kidney disease (CKD) diagnosis and monitoring. A retrospective study was conducted, including medical data from cats consulted between 2016 and 2018 in a veterinary teaching hospital and submitted to at least one UPCR measurement. A total of 140 cats were included: 35% non-proteinuric (UPCR < 0.2), 25% borderline proteinuric (0.2 < UPCR < 0.4), and 40% overtly proteinuric (UPCR > 0.4). In contrast to other studies, there was no association between UPCR and male reproductive status. UPCR was mainly requested for CKD diagnosis and monitoring. Correlation between UPCR and combined results from dipstick tests and USG was low and inconsistent. Proteinuric CKD cats had a worse outcome at both 6 (odds ratio (OR 4.04) and 12 months (OR 4.36)), and this finding was more pronounced for severely proteinuric cases in which the OR for death was 4.36 and 6.00 at 6 and at 12 months, respectively. In addition to reinforcing the negative prognostic value of proteinuria, this study stresses the low and the inconsistent agreement between UPCR and the combined results of dipstick tests and USG in cats.